2003
DOI: 10.1080/09674845.2003.11783682
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of trophoblast invasion-associated genes in the pre-eclamptic placenta

Abstract: The primary pathology of pre-eclampsia is thought be a defect in placentation due to failure of trophoblast invasion. Here, we aim to identify the expression profile of invasion-associated genes in the pre-eclamptic placenta. Messenger RNA (mRNA) expression levels of extracellular matrix molecule-related genes in five pre-eclamptic placentas and in five strictly matched normal placentas were assayed using complementary DNA (cDNA) microarrays representing over 220 human cytokine-associated or hormone-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
0
29
1
2
Order By: Relevance
“…Therefore, defining the gene expression of preeclamptic placentas has been the focus of numerous studies (Damiano, 2011;Ornaghi et al, 2011;Shin et al, 2011;Wang et al, 2011). To our knowledge, a number of comprehensive analyses have been conducted on the gene expression in preeclamptic placentas using DNA microarrays Pang and Xing, 2003a, 2003b, 2004Reimer et al, 2002;Sitras et al, 2009;Tsoi et al, 2003;Zhou et al, 2006). These studies revealed a substantial number of molecular players involved in the process of preeclampsia development, and helped defined the role of some of the signaling pathways involved in the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, defining the gene expression of preeclamptic placentas has been the focus of numerous studies (Damiano, 2011;Ornaghi et al, 2011;Shin et al, 2011;Wang et al, 2011). To our knowledge, a number of comprehensive analyses have been conducted on the gene expression in preeclamptic placentas using DNA microarrays Pang and Xing, 2003a, 2003b, 2004Reimer et al, 2002;Sitras et al, 2009;Tsoi et al, 2003;Zhou et al, 2006). These studies revealed a substantial number of molecular players involved in the process of preeclampsia development, and helped defined the role of some of the signaling pathways involved in the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Although this may be reasonably straightforward for diseases such as cancer, where samples of affected and healthy tissue can be taken from the same patient, conditions such as pre-eclampsia are more difficult, since variation between individuals has also to be taken into account. A PubMed search identified nine studies published between 2002 and 2005 which have used microarrays to compare placental gene expression in pre-eclamptic and normotensive pregnancy [93][94][95][96][97][98][99][100][101]. However, the lists of genes produced by each study show a discouraging lack of overlap.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…For example, Crespi & Semeniuk (2004) describe the evidence for positive selection on other genes associated with placentation, and Lecuit et al (2004) show how a bacterial pathogen can cross the human maternofoetal barrier via a process mediated in part by E-cadherin. Second, given that some of the cadherins involved in maternal-foetal interactions are also known to be expressed in other tissues, they may have been subject to positive selection in other contexts, such as regulation of development (Noonan et al 2003;Wheelock & Johnson 2003) or the evolution of vulnerability to preeclampsia (Pang & Xing 2003) or cancer (Ilyas 2000;Hirohashi & Kanai 2003).…”
Section: Resultsmentioning
confidence: 99%